Emotion dysregulation and eating disorder outcome: Prediction, change and contribution of self‐image. (25th March 2022) - Monell, Elin; Clinton, David; Birgegård, Andreas
Abstract: Objectives: Eating disorders (EDs) are severe disorders with unsatisfactory outcome. Emotion dysregulation and self‐image are suggested maintenance factors; this study examined emotion dysregulation as potential predictor and/or mechanism of change in relation to ED outcome, and associations between change in emotion dysregulation and self‐image in relation to outcome. Design: Registry data from initial and 1‐year follow‐up assessments for 307 patients with a wide range of EDs in specialized ED treatment were used. Methods: Initial and change (∆) in emotion dysregulation were examined as predictors of 1‐year outcome. Direct and indirect associations between ∆emotion dysregulation and ∆self‐image as either independent variable or mediator in relation to ∆ED psychopathology as dependent were also examined. Results: Higher initial emotion dysregulation was weakly associated with higher follow‐up ED psychopathology, but not remission, while relative increase in emotion dysregulation was associated with both higher follow‐up psychopathology and increased risk of still having a diagnosis. Change in emotion dysregulation primarily had an indirect effect (through change in self‐image), while change in self‐image had a direct effect, on change in ED psychopathology improvement (such that improvement in one was associated with improvement in the other). Conclusions: Results identify emotion dysregulation as a potential mechanism of change in relation to ED outcome. However, this association was mainly mediated by change in self‐image. Results indicate that, in order to improve emotion regulation as a means to reduce ED psychopathology, improving self‐image is essential.